Thermoresistive Thin Film Flow Sensor. (1989) - Berlicki, T. M.; Murawski, E.; Osadnik, S. J.; Prociòw, E. L.
Abstract : Some technological aspects and basic parameters of nickel thin film gas flow sensors are presented. Thermal conditions of sensors are described by the mechanisms of heat transfer. Typical characteristics measured during the sensor operation are given.